Factors associated with hopelessness, depression and anxiety in the Honduran-Central America population during the COVID-19 pandemic - Espinoza-Turcios, Eleonora; Gonzales-Romero, René Mauricio; Sosa-Mendoza, Carlos; Sierra-Santos, Manuel; Castro-Ramos, Henry Noel; Zambrano, Lysien Ivania; Armada, José; Mejía, Christian R. (Frontiers in Psychiatry, 2023)
Introduction: The mental health of the population has been affected by COVID-19, reporting in many populations higher levels of depressive, anxious and stress symptoms, however, in Honduras there are no studies showing the impact of COVID-19 on the mental health of the population. Aim: To determine the factors associated with hopelessness, depression and anxiety in times of COVID-19 in the Honduran population. Methods: Cross-sectional analytical study. Three scales were used, Beck for hopelessness, Hamilton for depression and anxiety, through interviews with the population attending different levels of health care throughout the country. Descriptive and analytical statistics were obtained. Results: Of the 8125 participants, there was less hopelessness among women (p=0.004), university students (p<0.001), but greater among those who had a family member deceased by COVID-19 (p<0.001), among those who had diabetes mellitus (DM) (p<0.001), history of mental illness (p<0.001) or had consumed drugs in the last six months (p<0.001). There was more depression among those with arterial hypertension (p=0.002), obesity (p=0.019), DM (p=0.004), history of mental illness (p<0.001) or had consumed drugs in the last six months (p<0.001). There was more anxiety among those infected with COVID-19 (p=0.023), according to having a family member deceased by COVID-19 (p=0.045) and in those with a history of mental illness (p<0.001). Discussion: The Honduran population presented important differences in the socio-pathological, according to the loss of family members or having previous illnesses, this according to the presentation of problems in the mental sphere. Conclusion: We found factors associated with hopelessness, depression and anxiety in times of COVID-19 in the Honduran population.